Feeding Management of Poultry in High Environmental Temperatures - Diarra , S.S.; Tabuaciri, P. (International Journal of Poultry Science, 2014)
Poultry can only regulate their body temperature within a narrow range of environmental temperatures (between 16-26°C). In the tropics, environmental temperatures are usually above this zone during most part of the year. High ambient temperatures adversely affect the performance of poultry with meat-type birds being more susceptible than egg-type birds. The poor performance of poultry under high ambient temperatures is mainly as a result of decreased feed intake which consequently reduces growth and meat quality, egg production and egg quality and efficiency of feed utilization. Several feeding practices have been used to alleviate the adverse effects of high temperatures on poultry performance. Although most studies on nutritional management of heat stress have been carried out in broilers there are also few reports on nutritional management in laying hens under heat stress condition. Feed form (particle size, moisture content), nutrient manipulation (especially energy and protein), electrolyte and vitamin supplementation, feeding time/feed restriction, choice feeding and drinking water management have all proven to be beneficial to heat-stressed poultry. The present paper reviews some common feeding management practices used to alleviate the effect of high ambient temperatures on poultry performance as well as their limitations.